An integrated strategy to improve the microclimate regulation of green-blue-grey infrastructures in specific urban forms. (20th October 2020) - Li, Jing; Wang, Yafei; Ni, Zhuobiao; Chen, Shaoqing; Xia, Beicheng
Abstract: Local microclimate and human thermal comfort are very sensitive to urban form. This study proposes an integrated strategy for urban infrastructures in different urban forms to investigate the importance of green-blue-grey infrastructure design in passive cooling and improving thermal comfort. Field measurements and model simulations have been conducted in three urban functional areas (i.e., a cultural square, park, and residential district) in Guangzhou. Twelve scenarios in two categories (i.e., adding and replacing) were investigated. The results show that, with the lowest coverage ratio of green infrastructure, the cultural square had a higher air temperature, which was 0.9 °C and 1.3 °C higher than the air temperatures in Ershadao park and the residential area, respectively. After removing the trees, the proportion of "extremely hot" thermal sensations in the park and residential area increased by 12.0% and 10.4%, respectively. Additionally, the types of infrastructures suitable for different urban forms are site specific. Specifically, in terms of cooling, the grey infrastructures performed better in the square and park, while the green infrastructures were most suitable for residential districts. The integrated scenarios (adding grey infrastructures and replacing green with grey infrastructures) revealed that the daily average air temperature in the square and park could be reduced by 0.63 °C and 0.26 °C, respectively, yet replacing the current green infrastructures with blue and grey infrastructures would aggravate heat stress in the residential area. The results of this study suggest that, in urban design, various infrastructures should be integrated and coordinated based on the characteristics of the specific urban form. This study can also assist urban designers in designing and planning green-blue-grey infrastructures that are more effective in maximizing thermal comfort in different urban functional areas. Graphical abstract: Image 1 Highlights: Cooling effects of blue, green and grey infrastructures were analyzed. Optimal designs of infrastructures for different functional areas were proposed. Grey infrastructure showed better cooling performance in square and park. Green infrastructure was the most suitable type for residential district. Integrated design of infrastructures should be applied in different functional areas.